Efeito do uso de vernizes com alta e baixa concentração de fluoreto suplementado com trimetafosfato sobre a abrasão da dentina bovina: estudo in vitro - Ramos, Jéssica Paula [UNESP] (2013)
The current study evaluated the effectiveness of fluoride varnishes supplemented or not with trimetaphosphate (TMP) on dentin abrasion. Polished bovine dentin discs (n = 60; diameter of 4 mm) were selected by the surface microhardness (SMH). Then, they were divided into 5 groups (n = 12) according to the type of varnish used: placebo (no F / TMP), 5% NaF varnish (5% NaF), 2.5% NaF varnish (2.5% NaF), 2.5% NaF varnish associated with 5% TMP (2.5% NaF + 5% TMP), 5% NaF varnish associated with 5% TMP (5% NaF + 5% TMP). The erosive challenge was promoted by citric acid (0.05 M, pH = 3.2) for 5 minutes (4 times daily) for a period of 5 days in addition with an abrasive treatment by mechanical brushing for 15 seconds for a period of 5 days. Then, after the challenge, the enamel damage (μm) was determined. To analyze the data, the type of experimental varnish was considered as the variation factor and the dentin surface damage (μm) as the measurement variable. The data was subjected to variance analysis (one-criterion) followed by Student-Newman-Keuls test (p<0.05). There was not any statistical difference between the groups in the SMH analysis (p>0.05). The groups with 2.5% NaF + 5% TMP and 5% NaF + 5% TMP showed the lowest damage values compared to the other groups (p<0.05). Moreover, the groups 2.5% NaF and 5% NaF presented similar damage (p>0.05). Thus, the results suggest that it is possible to reduce the dentin abrasion supplementing fluoride varnish with sodium trimetaphosphate